Analysis of thin - walled frame structure / Rahman Slamat - Slamat, Rahman (1996)
The analysis of engineering structures provides a natural introduction to Finite Element Methods. In this project the analysis of thin-watted open channel section structures with different angle of discontinuity is considered. The structure to be analysed composed of two parts loaded member and unloaded member. The length of loaded member is approximately 1922 mm and 920 mm length of unloaded member. The software that being used in this project is ANSYS (ANALYSIS SYSTEM). To make a comparison on the theoretical result obtained by ANSYS the DEVELOPED PACKAGE (BY MOHD. RAZALI IBRAHIM, NOV 1995) was used. The package was developed by using FORTRAN LANGUAGE. Analysis by ANSYS using shell element whereas for DEVELOPED PACKAGE the line element analysis is chosen.